Mengatasi Tantangan Kapasitas Produksi melalui Pendekatan Theory of Constraints dan Overall Equipment Effectiveness : Studi Kasus PT. Garut Makmur Perkasa - Mauluddin, Yusuf; Nugraha, Cecep Nurdin (Jurnal Kalibrasi, 2025)
This research is focused on overcoming the production capacity problems faced by PT Garut Makmur Perkasa (GMP). The main objective of this research is to increase the company's production capacity by overcoming bottlenecks that occur in the production process. The methodology used involves Theory of Constraints (TOC) and Overall Equipment Effectiveness (OEE) approaches as the main methods, which are supported by other analytical tools. In the initial stage, an evaluation was conducted of the workflow to identify bottlenecks occurring in the lot preparation, soaking-liming, delimming-tanning, and retanning processes. The analysis revealed that capacity differences in the production system resulted in the backlog of work in some areas, limiting overall production performance. The results of the calculations and analysis showed that the necessary solutions included the addition of labor and machinery at certain stages. Recommendations included the addition of 6 workers in the lot preparation area, procurement of 2 new machines in the soaking-liming and delimming-tanning processes, and one additional retanning machine. The main contribution of this research is to provide practical guidance for GMP in optimizing operational efficiency and productivity. The long-term implication of implementing this solution is the potential for increased production capacity, improved resource utilization efficiency, and improved company performance.